Using Odd-Alkanes as a Carbon Source to Increase the Content of Nutritionally Important Fatty Acids in Candida krusei, Trichosporon cutaneum, and Yarrowia lipolytica - Olga Matatkova; Lucia Gharwalova; Michal Zimola; Tomas Rezanka; Jan Masak; Irena Kolouchova (International Journal of Analytical Chemistry)
We investigated the possibility of utilizing unusual carbon sources by three yeast strains: Candida krusei DBM 2136, Trichosporon cutaneum CCY 30-5-10, and Yarrowia lipolytica CCY 30-26-36. These strains are characterized by high biomass yield, ability to accumulate high amounts of lipids, and their potential as producers of dietetically important fatty acids. The aim of this work was the production of nutritionally important fatty acids by utilization of n-alkanes with an odd number of carbon atoms, alone and in combination with glucose and subsequent analysis of microbial lipids accumulation and fatty acid profile. All three yeast strains were able to grow and produce high amounts of the fatty acids of interest. Yarrowia lipolytica was found as the most suitable strain for the growth on n-alkanes (n-pentadecane and n-heptadecane) as the only source of carbon. The addition of biosurfactants rhamnolipids into the cultivation increased the ratio of heptadecenoic acid (up to 17.9% of total FAs in Y. lipolytica CCY 30-26-36, 14.9% in T. cutaneum CCY 30-5-10, and 17.5% in C. krusei DBM 2136) and the total biomass yield. The results show that, by manipulation of the initial cultivation conditions, the ratio of important fatty acids may be increased.